PEMBATALAN PERKAWINAN DISEBABKAN ADANYA PEMALSUAN IDENTITAS DITINJAU DARI UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN DAN KOMPILASI HUKUM ISLAM (STUDI KASUS PADA PUTUSAN NOMOR 435/PDT.G/2013/PA MEDAN) - YUNESIA PINGKANITA PELAWI PINGKANITA PELAWI (PREMISE LAW JURNAL, 2015)
Article 22 of Law No. 1/1974 on Marriage states that “a marriage can be cancelled when the parties concerned does not fulfill the requirements for a marriage. ”When one or some of the requirements is missing, the marriage is invalid. The forgery of identity, especially of the status of the groom or bride -to-be, for getting married commonly occur today, and the incidence of forgery can happen anywhere. One of the examples about the forgery of identity in marriage which causes the cancellation by the Religions Court Class IA, Medan, is the case No. 435/Pdt.G/2013/PA.Mdn. Therefore, it is necessary to study the responsibility of P3N (Assistant Registrar of Marriages) since there is a complaint about marriage cancellation because of forgery of identity, the judge’s consideration in the Religious Court, Medan, on marriage cancellation, and legal consequence of the marriage cancellation according to the Verdict No. 435/Pdt.G/2013/PA.Mdn. PPN (Registrar of Marriages) and P3N (Assistant Registrar of Marriages) had the authority/responsibility to forestall or to cancel a marriage which did not fulfill the requirements, including the forgery of identity of groom or bride-to-be. When the P3N violated this regulation, he could be charged with criminal proceedings as the collaborator of forging of document. Legal consequences of marriage cancellation were as follows: first, the cancellation of the Book of Marriage Certificate No. 609/73/VII/2012 on July 20, 2012; secondly, there was no iddah for a wife whose marriage was cancelled; thirdly, joint property was owned by each party, the child was considered legitimate and had the right to be taken care of (hadhanah) by the father, and had the right to have guardianship and to be an heir. Keywords: Legal Consequence, Marriage Cancellation, Forgery of Identity